Existence of Fiber Bragg Grating Sensors Based on Power Input and Transmission Distance - Saktioto, Saktioto; Bintang, Shantela Hanna Mastaria; Emrinaldi, Tengku; Zamri, Zamri; Samudra, Mohd Rendy; Soerbakti, Yan (The Physical Society of Indonesia, 2025)
Optical fiber was chosen as a transmission medium because of its ability to transmit data with high power, high speed and low attenuation. Despite these advantages, optical fiber still faces challenges such as attenuation and dispersion which can reduce data transmission performance. This research examines the performance of fiber optic-based communication systems using fiber Bragg grating (FBG) sensors, especially in overcoming linear effects that affect transmission quality. In designing this system, researchers varied the transmission distance from 10 – 150 km, and adjusted the input power from 2 – 20 dBm. The research results show that uniform FBG is more effective in improving signal quality and reducing transmission errors compared to Gaussian FBG. The use of FBGs on coarse wavelength division multiplexing (CWDM) channels also improves system performance, with better quality factors and reduced bit error rates (BER). However, at a distance of more than 60 km, the signal quality decreases due to high noise, which also reduces the Q-factor value, the Q-factor value drops significantly from 61.7699 to 3.0866. Overall, uniform FBG provides more stable and robust data transmission, and increases transmission capacity compared to Gaussian FBG